EFEKTIVITAS PENGELOLAAN SURAT MASUK DAN SURAT KELUAR DI BAGIAN URUSAN TATA USAHA RUMAH SAKIT MATARAM - Tia Nadila; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Management of Incoming and Outgoing Correspondence: Work Effectiveness in the Administrative Affairs Department at Mataram Hospital The research method used was qualitative descriptive. Data collection techniques included observation, interviews, and literature review, with a purposive sampling technique. The research was conducted in March and April 2023 with a sample size of 4 out of 717 administrative staff members. The study found that the administrative affairs department had processed 217 incoming letters and 461 outgoing letters. This research identified several issues in the management of incoming and outgoing letters, including a lack of adequate equipment and supplies, as well as challenges related to staff work efficiency and human resources. Based on the identified issues, the author offers the following recommendations: the addition of equipment and supplies to optimize the management and archiving of correspondence; processing correspondence on a regular basis to prevent backlogs, given that manual processing is prone to delays; and the addition of staff—specifically a head of administrative affairs (a role currently handled by the head of general administration) and an archivist capable of effectively managing correspondence archives effectively to ensure more efficient management.